Periventricular nodular heterotopia and bilateral intraventricular xanthogranulomas in 22q11.2 deletion syndrome - Moogeh Baharnoori; Daniel M. Mandell; Danielle M. Andrade; Eva W.C. Chow; Anne S. Bassett; Tim-Rasmus Kiehl (Elsevier, 2017)
22q11.2 deletion syndrome (22q11DS) is the most common pathogenic copy number variant in humans. Neuropsychiatric phenotypes, including schizophrenia, are prominent. Imaging studies of individuals with this syndrome show a variety of abnormalities that may indicate abnormal neuronal migration. Here we present the neuroimaging and neuropathologic features of a 22q11DS patient with bilateral periventricular nodular heterotopias (PNH) and intraventricular xanthogranulomas that were identified by post-mortem examination. Keywords: 22q11.2 Deletion Syndrome, periventricular nodular heterotopia, neuronal migration, xanthogranuloma